Chamber miniaturization for four terminal electrical impedance spectroscopy (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: Using smaller chambers for four terminal electrical impedance measurements significantly reduces the costs. The cost reduction accumulates due to the use of less sample volume and less printing material for production. Especially, sample material for biological cell experiments is very expensive. Furthermore, the preparation time decreases since less cells needs to be grown for experiments. Another advantage is that small changes inside the sample volume have a higher impact on the output and by that the sensitivity is higher. The long term goal is to be able to measure single cells.Materials and Methods: The Form 2 stereolithography apparatus (SLA) of the company Formlabs GmbH is used with a possible printing resolution of 25 µm. The printer uses an ultraviolet (UV) laser to project a pattern onto the resin. The resin is a transparent and viscous photopolymer. Photopolymers set under UV light. Thus, the pattern of the UV light projected on the resin is one slice of the 3D model. After the printing process, the object has to be cleaned and post processed.Results and Discussion: A chamber system with a total volume of 12.4 ml was miniaturized to a chamber with 0.4 ml including a reservoir of sample medium. Smaller chamber systems were stronger influenced by vanishing of medium since the sensitivity is increased. To avoid a change of the measured volume while measuring the impedance, a reservoir is established.Conclusion: Costs for production and samples is reduced, the preparation time is minimized and the sensitivity is enhanced. Further, a challenging effect for miniaturization, namely fast liquid evaporation in smaller volumes, is identified. It is solved by introducing the reservoir of medium above the measurement volume.